An exploration study to detect important factors influencing on learning oriented customers - Naser Azad; Sima Zomorrodian (Management Science Letters)
The recent advances in technology have increased learning channels in industry helping organizations remove the middle level management. This paper presents an empirical investigation to study the role of different factors influencing on learning oriented customers. The study designs a questionnaire and distributes it among 200 randomly selected regular customers of a chain store named Shahrvand located in city of Tehran, Iran. Cronbach alpha is equal to 0.935, which is well above the minimum acceptable level. Using principle component analysis, the study has detected six factors including learning management, strategy, learning tools, learning approaches, human related factors and learning spirit.